Hello Stranger - Kleypas, Lisa (New York, NY : Avon Books, an imprint of HarperCollinsPublishers, 2018)
Dr. Garrett Gibson, England's only female physician, and Ethan Ransom, a former Scotland Yard detective with mysterious loyalties, share a one-night stand before becoming embroiled in a dangerous mission that is complicated by their growing feelings for one another.
Keywords: Women physicians -- Fiction -- England; Detectives -- Fiction -- England; Nobility -- Fiction; Aristocracy (Social class) -- Fiction; London (England) -- Fiction -- Social life and customs -- 19th century; Regency fiction; Historical fiction; Romance fiction